CHARACTERISTICS OF THE SYSTEM OF VALUES IN OLD AGE - Jumaeva , Guljahon O‘ralovna (Educational Research in Universal Sciences, 2024)
This article describes the concept of value, features of the formation and manifestation of personal values, the value system of older people, changes in the system of value orientations throughout a person’s life, including in old age, and its socio-psychological factors. In order to determine the uniqueness of the value orientation in older people, studies conducted using the method of diagnosing value orientations by S. Schwartz and their results are described.